L’orpaillage au Burkina Faso : une aubaine économique pour les populations, aux conséquences sociales et environnementales mal maîtrisées - Joseph Bohbot (EchoGéo)
This article focuses on the issues raised by the local gold mining industry in Burkina Faso. The small-scale extraction of gold of is today one of the pillars of the economy of this poor state of West Africa. However, the gold mining results in the destructuring of the social fabric and the degradation of the environment. The discovery of a gold lode generates massive migrations to mining sites and the creation of makeshift camps. Far from the cities, the miners and their families are deprived of social and sanitary infrastructure and live in great precariousness. Finally, the environment around the mines is durably polluted by the techniques of extraction of gold (use of mercury or cyanide). Nevertheless, we will see that more environmentally and population-friendly initiatives are now being tested in Burkina Faso.